2016
DOI: 10.3892/br.2016.815
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic effect of serum miR-196b as biomarker in colorectal cancer

Abstract: The microRNA, miR-196b, serves a role in normal cell differentiation, proliferation and tumorigenesis of different types of cancer. The aim of the present study was to explore the serum expression of miR-196b in colorectal cancer (CRC) and its correlation with clinicopathological features. Sera samples were obtained from 103 patients with CRC, 51 patients with colorectal adenoma (Ad) and 100 healthy individuals for the present study. The serum expression of miR-196b in sera samples of the three cohorts was det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…Although they vary in expression levels, the miR-196 family of molecules is consistently overexpressed in oral cavity, esophageal, stomach, and intestinal cancer tissues [ 35 ]. Several investigations [ 36 38 ] support our findings that miR-196b expression levels in malignant tissues are significantly higher than in adjacent normal colorectal mucosa. MiR-196b-5p was also found to be elevated in serum exosomes of CRC and is associated with liver metastasis [ 35 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Although they vary in expression levels, the miR-196 family of molecules is consistently overexpressed in oral cavity, esophageal, stomach, and intestinal cancer tissues [ 35 ]. Several investigations [ 36 38 ] support our findings that miR-196b expression levels in malignant tissues are significantly higher than in adjacent normal colorectal mucosa. MiR-196b-5p was also found to be elevated in serum exosomes of CRC and is associated with liver metastasis [ 35 ].…”
Section: Discussionsupporting
confidence: 87%
“…MiR-196b-5p was also found to be elevated in serum exosomes of CRC and is associated with liver metastasis [ 35 ]. MiR-196b-5p is also more upregulated in serum of patients with CRC compared to that in adenoma patients or healthy individuals [ 36 ]. A few reports have shown that the miR-196 family can also act as tumor suppressors.…”
Section: Discussionmentioning
confidence: 99%
“…This correlation was also remarkable in TNM stage II CRC patients, showing that miR-21 expression may be a beneficial early stage biomarker to determine subjects at high risk of tumor invasion that have no evidence for metastasis disease. 43,44 Furthermore, several studies have revealed overexpression of miR-17-3p, 45 miR-92a, 46 miR-1290, 47 miR-210, 23 miR-183, 48 miR-885-5p, 49 miR-592, 50 miR-196b, 51 or miR-155 52 correlated with lower poor progression-free survival (PFS) or OS. It is considerable to mention that low-expressed miRNAs have also been correlated with a poor prognosis in CRC.…”
Section: Circulating Mirnas In Crc Prognosismentioning
confidence: 99%
“…Interestingly, a significant correlation between plasma miR-221 level and p53 protein expression was found but the role of miR-221 in the regulation of p53 is nowadays unknown [54]. Further, several works have found high levels of miR-17-3p [55], miR-106a [55], miR-21 [56], miR-92a [57], miR-1290 [58], miR-210 [59], miR-183 [60], miR-885-5p [42], miR-592 [61], miR-196b [62] or miR-155 [63] associated with lower PFS or OS. More recently, serum miR-203 has been proposed as another promising prognostic and metastasis-predictive biomarker in CRC.…”
Section: Mirnas As Prognostic Biomarkers In Crcmentioning
confidence: 99%